2012
DOI: 10.1093/nar/gks1307
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of the C-terminal domain of Mycobacterium tuberculosis leucyl-tRNA synthetase in aminoacylation and editing

Abstract: The C-terminal extension of prokaryotic leucyl-tRNA synthetase (LeuRS) has been shown to make contacts with the tertiary structure base pairs of tRNALeu as well as its long variable arm. However, the precise role of the flexibly linked LeuRS C-terminal domain (CTD) in aminoacylation and editing processes has not been clarified. In this study, we carried out aspartic acid scanning within the CTD of Mycobacterium tuberculosis LeuRS (MtbLeuRS) and studied the effects on tRNALeu-binding capacity and enzymatic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Binding of the Anticodon Controls tRNA Aminoacylation Activity-The C-terminal residues of aaRSs are sometimes essential for the enzymatic activity (48,49). In E. coli tRNA Thr , all of the bases from 32 to 37 interact through at least one hydrogen bond to the protein, and bases 35-38 are splayed out from the anticodon loop (14), indicating that the tRNA recognition cleft is a mobile region.…”
Section: A Genetic Screen To Identify Functional Elements In Thrrs-mentioning
confidence: 99%
“…Binding of the Anticodon Controls tRNA Aminoacylation Activity-The C-terminal residues of aaRSs are sometimes essential for the enzymatic activity (48,49). In E. coli tRNA Thr , all of the bases from 32 to 37 interact through at least one hydrogen bond to the protein, and bases 35-38 are splayed out from the anticodon loop (14), indicating that the tRNA recognition cleft is a mobile region.…”
Section: A Genetic Screen To Identify Functional Elements In Thrrs-mentioning
confidence: 99%
“…Although several conserved, positively charged residues were identified within the CTD of EcLeuRS, none of them provided site-specific interaction with tRNA Leu (28). (10,27). In addition to the three key lysine residues, the C-terminal five residues of CaLeuRS may maintain the proper conformation of the CTD during leucylation but not interact with tRNA Leu directly, which contrasts with archaeal PhLeuRS (10).…”
Section: Discussionmentioning
confidence: 99%
“…In EcLeuRS, Ala or Asp mutations of several conserved residues had only minimal effects on the aminoacylation activity as did the corresponding double and triple sites mutants (28). In another bacterial LeuRS, Mycobacterium tuberculosis LeuRS (MtLeuRS), several residues were shown to maintain the hydrophobic environment to stabilize the conformation of its CTD and to orient the tRNA (27 Leu has been studied extensively by structural and biochemical methods, the potential role of the CTD of eukaryotic LeuRSs in the recognition of tRNA Leu has never been reported. Here, our results first showed that CTD of CaLeuRS (CaCTD) is indispensible for leucylating both CatRNA Ser (CAG) and CatRNA Leu (CatRNAs).…”
mentioning
confidence: 99%
“…Bovine serum albumin was used as a negative control to reflect that there was no fluorescence response to tRNA. The k d values were calculated by "one special binding equation" according to fitting fluorescence intensity change data vs. tRNA concentration, using Graphpad Prism software (Hu et al 2013). …”
Section: Preparation Of Proteins and Trnamentioning
confidence: 99%